Immigration to Norway 1969-2010. Effects of policies and EEA membership - Ådne Cappelen; Terje Skjerpen (Statistics Norway, Research Department, 2012)
We examine how changes to regulations and the economic conditions have influenced gross immigration to Norway from, in principle, all countries in the world during 1969- 2010. In line with existing studies of immigration we find that economic factors were important for immigration to Norway. Income differences between Norway and other countries have the expected impact, as do changes in income distributions. The labour market situation has also been important in that lower unemployment in Norway has resulted in higher immigration and higher unemployment in the country of origin has led to higher emigration to Norway. We find that immigration policies have largely had the expected effects. One example is the 1975 'immigration halt' that did have a strong and long lasting effect on total immigration to Norway. Further tightening of the immigration regulations that came in 1977 also reduced immigration, while the more liberal policies introduced in 1981 contributed to higher immigration. From 2000 to 2010 several changes linked to the enlargement of EU influenced immigration to Norway. Norway's membership in the European Economic Area (EEA) in 1994, and in the Schengen-area in 2001 resulted in higher immigration while the 2004 and 2007 EU enlargements also increased labour immigration to Norway substantially.
Keywords: J11; J15; 330; Immigration; Immigration policies; Incentive variables